GC-MS analysis and antibacterial activity of ethanolic and water extracts of Malaysian Heterotrigona itama propolis against selected human pathogenic bacteria - Mohd Zohdi, Rozaini; Adli, Muhammad Amirul; Mohsin, Hanis Fadzillah; Muhamad Mokhtar, Shahida; Muhammad Low, Anis Low; Awang Junaidi, Awang Hazmi; Jahrudin, Dzu Hendra Ja (Malaysian Society of Applied Biology, 2023)
Despite the growing interest in the therapeutic potential of propolis, limited attention has been paid to the chemical composition and biological activity of water extract propolis produced by Malaysian stingless bees. Thus, this study aimed to determine the phytochemical composition and antibacterial potential of ethanolic extract propolis (EEP) and water extract propolis (WEP) of the stingless bee species, Heterotrigona itama against ten pathogenic bacteria. The phytochemical analysis of the extracts was carried out using the gas chromatography-mass spectrometry (GC-MS) technique. The antibacterial activity was determined using the disc-diffusion, minimum inhibition concentration (MIC), and minimum bactericidal concentration (MBC) methods. The GC-MS analysis of EEP exhibited four volatile compounds including hexamethylcyclotrisiloxane, 2-hydroxy-2-cyclopenten-1-one, 2-coumaranone, and diethyl bis(trimethylsilyl) ester silicic acid. However, only two compounds were identified in WEP, consisting of 2-(acetoxymethyl)-3-(methoxycarbonyl)biphenylene, and hexamethylcyclotrisiloxane. EEP showed the highest antibacterial activity against all Gram-positive bacteria (Bacillus subtilis, Enterococcus faecalis, Enterococcus faecium, Micrococcus luteus, Staphylococcus aureus, Streptococcus mutans) with values of the inhibition zones ranging from 7 to 10 mm. However, both extracts showed no antibacterial activity against Gram-negative bacteria, except WEP, which displayed an inhibition zone of 9.33 ± 1.53 mm against Escherichia coli. Meanwhile, EEP showed the lowest MIC and MBC values against M. luteus at 70 and 280 μg/mL, respectively. The results revealed the presence of several volatile compounds in the EEP of H. itama which could contribute to its antibacterial activity, particularly against Gram-positive bacteria.